Essence-Subjected Combinatorics of Law - NIKODIMOV, Igor Yu.; BURMISTROV, Igor A.; SINYUKOVA, Tatyana N.; MIRONOVA, Elena A. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The relevance of the paper is caused by the current collision between the will of the international political-economic groups and the will of the ruling circles in the legal area. The objective of the paper is to analyze the essence-subject combinatorics of law. The authors have established two main aspects of the legal concept and four main groups of the subjects of law. Finally, they have revealed sixteen combinations based on the concepts and levels of the subjects. Notably, the level of the subject of law as an individual consists of more than 7 billion subjects, so it is impossible to count the real number of combinations. But practically in the majority of cases, lawyers prioritize the will of an individual, a social group and the ruling circles, based on which the integral law is defined.